Time shift TDT timing acquisition algorithm for PPM-UWB - XIANG Xin1; TIAN Bin1; YI Ke-chu1; LIU Lei1 (Tongxin xuebao)
It was proved that the TDT （timing with a dirty template） blind timing algorithm was only suitable for PAM-UWB systems rather than PPM-UWB systems.Furthermore,a TS-TDT （time-shift-TDT） blind timing synchronization algorithm was presented for PPM-UWB,which got synchronizing information from calculating the delay cross-correlation values by means of two correlation branches.Theoretical analysis and simulation results demonstrate that the implementation of the algorithm is of low complexity and flexible in precision control.